Pengaruh Tunjangan Kinerja terhadap Kinerja Pegawai pada Kantor Kecamatan Pitumpanua Kabupaten Wajo - Lisnawati Lisnawati; Burhanuddin Burhanuddin; Ekayani Burhanuddin (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2026)
This study was conducted to examine the overview of the influence of performance allowances on employee performance. The main objective of this research is to analyze the extent to which performance allowances affect employee performance at the Pitumpanua District Office in Wajo Regency. This research employs a census method with a descriptive study design. Data collection techniques used include observation, documentation, and questionnaires. The population of this study consists of employees at the Pitumpanua District Office, Wajo Regency. Both descriptive and inferential statistical analysis techniques were applied to analyze the data. The study's results reveal that both performance allowances and employee performance at the Pitumpanua District Office fall within the